Exploration of teachers as a motivator in the teaching-learning process of English Language in students of tenth grade in "Isabel de Godin" High School academic year 2015-2016 - Guayanlema Chávez, Ivonne Gabriela (2017)
The present research was carried out in the "Isabel de Godín" School in which it was determined as a problem that the lack of motivation causes many students to not enjoy learning English because the teacher does not use the appropriate motivation strategies. This study describes how the teacher uses the motivation strategies used in English class. It was applied in the tenth year students of the "Isabel de Godín" School during the second chemistry of the 2015-2016 school years. The objective of this work was to explore the motivational strategies that the teacher as a motivator uses in the teaching-learning process of English. The type of study was qualitative of exploratory level. It was carried out with a population of 30 students and a teacher. The qualitative method is ethnographic. The technique used was non-participatory observation since as a researcher the role was passive and the instrument of data collection was an observation guide designed by the researcher. After the analysis, it was found that the main cause of student unconcern was the teacher does not use adequate motivation strategies and the students' interest in learning English is low.